Clozapine Reverses Dysfunction of Glutamatergic Neurons Derived From Clozapine-Responsive Schizophrenia Patients - Hribkova, Hana; Svoboda, Ondrej; Bartecku, Elis; Zelinkova, Jana; Horinkova, Jana; Lacinova, Lubica; Piskacek, Martin; Lipovy, Bretislav; Provaznik, Ivo; Glover, Joel C.; Kasparek, Tomas; Sun, Yuh-Man (Frontiers in Cellular Neuroscience, 2022)
The cellular pathology of schizophrenia and the potential of antipsychotics to target the underlying neuronal dysfunctions are still largely unknown. We employed glutamatergic neurons derived from induced pluripotent stem cells obtained from schizophrenia patients with a known history of response to clozapine and healthy controls to decipher the mechanisms of action of clozapine, spanning from molecular (transcriptome profiling) and cellular levels (electrophysiology) to observed clinical effects in living patients. Glutamatergic neurons derived from schizophrenia patients exhibited deficits in intrinsic electrophysiological properties, synaptic function and network activity. Deficits in K+ and Na+ currents, network behavior, and glutamatergic synaptic signaling were restored by clozapine treatment, but only in cells from clozapine-responsive patients. Moreover, neurons from clozapine-responsive patients exhibited a reciprocal dysregulation of gene expression, particularly related to glutamatergic and downstream signaling, which was also reversed by clozapine treatment. Our results underscore the importance of K+ and Na+ channels and glutamatergic synaptic signaling in the pathogenesis of schizophrenia and demonstrate that clozapine might act by normalizing perturbances in this signaling pathway. Only cell lines from clozapine responders improved their functioning and transcriptomic profile. To our knowledge this is the first study that demonstrated that hiPSC derived neurons carry the clinical phenotype – response to an antipsychotic. This finding opens a new avenue for the search for an effective treatment agent tailored to the needs of individual patients.